Serviços de representação, agregação e histórico de contexto ontológico em apoio ao desenvolvimento de aplicações - Veiga, Ernesto Fonseca (2016)
Context Management Systems (CMS) are responsible for processing the context throughout its life cycle, which is performed in four steps defined in the literature: acquisition, modeling, reasoning and dissemination. The modeling step has great relevance in this process, being responsible for transforming the data acquired from sensors in highlevel context. However, this step has been impacted by the increasing deployment of sensors and the large volume of information that is available, creating the need to provide services to carry out the handling of such information, providing adequate representation and supporting the development of applications. In this sense, the ontology-based representation has major advantages, including: high expressiveness, standardization and interoperability. Before highlighted requirements by the literature, this work presents the construction of services related to the context life cycle modeling step: representation, aggregation and history, based on ontologies. These services have been designed and implemented as components that integrated a CMS called Hermes. Therefore, the scope of this work is composed by: i) Hermes Widget: ontological representation of independent domain context, based on Stimulus-Sensor-Observation standard; ii) Hermes Aggregator: ontologically represented context aggregation and its conversion for application domains; and iii) Hermes History: context history for the different levels of expression produced by other components. These services have been validated and evaluated in a human vital signs monitoring scenario.